TELAAH FILSAFAT MORAL SEBAGAI DASAR PENGAMBILAN KEPUTUSAN ETIS DALAM AKUNTANSI - Andi Sri Kumala Putri P; Abdul Hamid Habbe; Gagarin Panggalung (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This article aims to examine the concept of moral philosophy as a conceptual basis in ethical decision-making in the accounting profession. The development of the business world and major ethics scandals such as Enron and WorldCom show that ethical failures can cause widespread social and economic harm. This requires accountants to not only have technical ability, but also a strong moral foundation. Ethical decision-making must be rooted in rational moral considerations, not simply formal adherence to professional standards. This research uses a qualitative method with a library research approach, examining scientific literature, professional codes of ethics, and classic works of philosophers. Data analysis is carried out by qualitative content analysis to identify, interpret, and synthesize moral concepts. The results of the study show that moral philosophy, which is generally divided into deontology, utilitarianism, and virtue ethics, provides a comprehensive framework of thinking for accountants. Deontology emphasizes the moral obligation to act honestly and fairly (integrity) regardless of the consequences. Utilitarianism assesses actions based on the greatest benefits to many parties, encouraging accountants to weigh the social impact of their decisions on a wide range of stakeholders. Meanwhile, the Virtue Ethics focuses on the formation of the accountant's character and personal integrity, ensuring that the accountant acts morally correct even without external supervision. These three theories fundamentally strengthen the five fundamental ethical principles set forth by the Code of Ethics of the Indonesian Institute of Accountants (IAI, 2022). Thus, an understanding of moral philosophy is essential to strengthen the basis of accountants' ethical considerations and increase public trust in the credibility of the profession.